2022
DOI: 10.3390/molecules27072134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aldose Reductase by Ginsenoside Derivatives via a Specific Structure Activity Relationship with Kinetics Mechanism and Molecular Docking Study

Abstract: This present work is designed to evaluate the anti-diabetic potential of 22 ginsenosides via the inhibition against rat lens aldose reductase (RLAR), and human recombinant aldose reductase (HRAR), using DL-glyceraldehyde as a substrate. Among the ginsenosides tested, ginsenoside Rh2, (20S) ginsenoside Rg3, (20R) ginsenoside Rg3, and ginsenoside Rh1 inhibited RLAR significantly, with IC50 values of 0.67, 1.25, 4.28, and 7.28 µM, respectively. Moreover, protopanaxadiol, protopanaxatriol, compound K, and ginsenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…From these data, it is predicted that GdAldRed is a viable target of LL and that LL presented a better binding affinity in the active site. In a review of studies of enzyme inhibition by terpene compounds, it was found that several members of the terpene family, such as ginsenosides (triterpene saponins), perillosides A and C (monoterpene glycosides) and triterpenes/meroterpenes from Ganodema lucidium (lanostane and farnesyl hydroquinone-triterpene conjugates), have the ability to inhibit AldRed from humans and other species [18][19][20][21]. This prompted us to predict whether the diterpene LL was able to interact and inhibit GdAldRed using molecular docking approaches.…”
Section: Resultsmentioning
confidence: 99%
“…From these data, it is predicted that GdAldRed is a viable target of LL and that LL presented a better binding affinity in the active site. In a review of studies of enzyme inhibition by terpene compounds, it was found that several members of the terpene family, such as ginsenosides (triterpene saponins), perillosides A and C (monoterpene glycosides) and triterpenes/meroterpenes from Ganodema lucidium (lanostane and farnesyl hydroquinone-triterpene conjugates), have the ability to inhibit AldRed from humans and other species [18][19][20][21]. This prompted us to predict whether the diterpene LL was able to interact and inhibit GdAldRed using molecular docking approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the 24(S)-OT saponins, vinaginsenoside R2, and majonoside R2 were metabolized to pseudoginsenoside RT4 cultured with mouse feces. 47 Generally, CK and Rh1 are the main metabolites of PPD or PPT-type ginsenosides, which have been reported to exhibit anti-inflammatory, 48 antioxidant, 7 antidiabetic, 6 antihypertension, 10 and other biological activities. The pharmacokinetic study unveiled that the metabolism capacity of the ginsenosides (such as the generation of CK) varied significantly among individuals.…”
Section: Development and Validation Of A Uhplc-smrmmentioning
confidence: 99%
“…Several categories of phytochemicals have been reported or isolated from the valuable Panax species. However, ginsenosides are regarded as the main bioactive ingredients, exhibiting antidiabetic, , anticancer, anti-inflammatory, antihypertensive, , and lipid-lowering effects . Consequently, they function as chemical markers for the quality control of ginseng. To compare the nature and content differences of different ginsenosides (qualitatively/quantitatively) among different ginseng extracts, as well as the differences in their metabolites generated by the intestinal microbiota, a profound understanding of their functional differentiations is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Aldose reductase (AR, EC 1.1.1.21) is a key aldo-keto reductase enzyme of the polyol pathway that catalyzes glucose to sorbitol, along with the parallel conversion of NADPH to NADP + [ 15 ]. Furthermore, sorbitol is converted to fructose by the presence of the sorbitol dehydrogenase enzyme, and that occurs in an NAD + -dependent manner [ 16 ]. AR is known to play key roles in the pathogenesis of diabetes-related complications such as neuropathy, nephropathy, and retinopathy [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…AR is known to play key roles in the pathogenesis of diabetes-related complications such as neuropathy, nephropathy, and retinopathy [ 17 ]. AR inhibitors, which are critical for managing factors involved in the onset and progression of DM, are also being developed [ 16 ]. Therefore, AR is an attractive target for researchers who are designing and developing drugs to treat and manage long-term diabetic complications.…”
Section: Introductionmentioning
confidence: 99%